2016
DOI: 10.11138/jts/2016.4.1.006
|View full text |Cite
|
Sign up to set email alerts
|

Opening-wedge high tibial osteotomy: a seven - to twelve-year study

Abstract: Purpose: medial opening-wedge osteotomy is a widely performed procedure used to treat moderate isolated medial knee osteoarthritis. Historically, the literature has contained reports showing satisfactory midterm results when accurate patient selection and precise surgical techniques were applied. this study was conducted to investigate the clinical and radiographic seven-to twelve-year results of opening-wedge high tibial osteotomy in a consecutive series of patients affected by varus knee malalignment with is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Consistent with these previous reports, the ISR of our patient decreased from 1.13 preoperatively to 0.97 postoperatively, and the position of the patella was lower after than before the surgery. Furthermore, an increased TSA due to OWHTO can cause limited knee extension ROM and knee joint pain [ 15 ], although a postoperative increase in the TSA was not observed in our patient. It is also possible that pain receptors were stimulated because OWHTO is a joint-sparing surgery that preserves biological tissue.…”
Section: Discussionmentioning
confidence: 61%
“…Consistent with these previous reports, the ISR of our patient decreased from 1.13 preoperatively to 0.97 postoperatively, and the position of the patella was lower after than before the surgery. Furthermore, an increased TSA due to OWHTO can cause limited knee extension ROM and knee joint pain [ 15 ], although a postoperative increase in the TSA was not observed in our patient. It is also possible that pain receptors were stimulated because OWHTO is a joint-sparing surgery that preserves biological tissue.…”
Section: Discussionmentioning
confidence: 61%
“…Severe PF OA is known as a contraindication of HTO. 12,13 However, the effect of PF chondromalacia on the result of HTO has not been clearly revealed yet. Therefore, the present study analyzed the effect of PF chondromalacia on radiographic and clinical outcomes following HTO.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographically, 96.6% of the patients obtained target correctional MTFA of 183 to 186 degree at the final follow-up visit. 12 Majima et al have assessed short-term (1 year after surgery) and long-term (10-15 years after surgery) results of 44 cases following HTO. They reported that the average knee function score was improved significantly from 59.1 points before surgery to 85.1 points at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…HTO has gained popularity in the treatment of isolated medial compartment osteoarthritis, especially in the younger age group. 1 5 12 By correcting the mechanical axis, it will allow redistribution of weight and hence off load the medial compartment and assist in cartilage regeneration. 13 14 However, patella baja is a well-known undesired result following HTO.…”
Section: Discussionmentioning
confidence: 99%
“…High tibial osteotomy (HTO) is a well described treatment in early medial compartmental osteoarthritis of the knee. 1 2 3 4 5 This procedure is especially useful in younger patients to offload the medial compartment of the knee by changing the mechanical axis. However, in the process of doing so, there is always a concern of the two common undesirable effects, namely, the patella height changes and posterior tibial slope (TS) changes post HTO.…”
Section: Introductionmentioning
confidence: 99%